Concentration od omega-3 PUFA extracted from yellow fin tuna (Thunnus albaceres) eyeballs by Lipase-catalyzed alcoholysis. - Braceros, Ma. Cecilia Esperanza Salgado
Fish oil extracted from the eyeballs of yellowfin tuna (Thunnus albacares) by the aqueous method of lipid extraction as modifies by Panggat (1997)